Tax Abuses as an Ethical Issue (The Journal of Forensic Accounting Profession, 2025)
This paper analyses tax abuses in the Federation of Bosnia and Herzegovina (FBiH), focusing on the shadow economy and undeclared work. The research aimed to identify the most widespread forms of tax evasion and the sectors in which they are most prevalent, as well as to examine the role of the Code of Ethics in combating these negative phenomena. The research findings show that the construction, hospitality, retail, and service sectors are the most affected by the shadow economy and undeclared work. The lack of consistent application of the Code of Ethics and legal regulations further contributes to the proliferation of these practices and undermines economic development and social stability. Recommended measures to combat tax evasion include strengthening monitoring and control, consistently applying the law, educating and raising public awareness, and promoting formal employment. Through the combined efforts of all relevant stakeholders - authorities, regulators, employers, employees, and civil society - significant progress can be made in reducing the shadow economy and undeclared work, promoting fair business practices, and achieving sustainable economic development.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2025-0004, pod licencom CC BY-NC-ND 4.0)
Keywords: tax abuses; ethics; business practices; Federation of Bosnia and Herzegovina